Can restless legs be a sign of something else? A case report of spondyloarthritis presenting with restless legs syndrome and a review of the literature - E. Yılmaz (PAGEPress Publications, 2023)
Restless legs syndrome (RLS) is a chronic movement disorder characterized by an urge or need to move the limbs, usually associated with uncomfortable sensations in the legs and sleep disorders. In general, two clinical forms of RLS are described: primary and secondary. Although primary RLS has a familial component, the underlying mechanism is still not fully understood but seems to be related to abnormalities in the dopaminergic and glutamatergic pathways of the central nervous system. The secondary forms of the syndrome are associated with iron deficiency, renal failure, pregnancy, diabetes mellitus, peripheral neuropathy, and several rheumatologic disorders such as rheumatoid arthritis and Sjögren's syndrome. In a few clinical trials, an increased frequency of RLS has been reported in patients with spondyloarthritis. In this report, a case of coexistence of spondyloarthritis and RLS is presented, showing satisfactory improvement with conservative treatment and additionally adding naproxen. Anemia of chronic disease occurring in rheumatic diseases, and associated iron deficiency may contribute to the development of RLS.